Experimental investigation of the effect of cutting tool coating on delamination during of milling Metal Matrix Composite (MMC) - Konneh, Mohamed; N. M. A., Rosli (2015)
Metal Matrix Composite (MMC) has become one of the materials that is known to have high hardness and abrasive nature, due to the presence of silicon carbide (SiC) inside the composite. The characteristic nature of the MMC results in unpredictable cutting tool performance when it comes to a machining process. In order to explore a better means of improving the cutting of this material, coated tools were used to mill a MMC laminate composite. Therefore, experiments were carried out to cut a MMC laminate plate of 50 mm x 50 mm x 2 mm using 4 mm-diameter carbide end mills coated titanium aluminum nitride (TiAlN), as it is believed that TiAlN is one of the coatings, that has unique properties such as lower friction, higher adhesion, higher resistance to wear and crack. Box Behnken design was used to plan the running of experiments. Three independent cutting parameters, spindle speed, feed rate and depth of cut with values ranging from 4500-7500 rpm, 100-250 mm/min and 0.25-0.75 mm respectively, were studied. Experimental results show that delamination of the machined MMC was influenced mostly by feed rate and the depth of cut.